Development of new levodopa treatment strategies in Parkinson's disease—from bedside to bench to bedside. (3rd April 2017) - Aquilonius, Sten-Magnus; Nyholm, Dag
Abstract: This review will illustrate the process of moving from an idea through preclinical research and Galenic developments into clinical investigations and finally to approval by regulatory agencies within the European Union. The two new treatment strategies described, levodopa/carbidopa intestinal gel and levodopa/carbidopa microtablets, for advanced Parkinson's disease, have been developed in collaborative research within departments at Uppsala University. With this historical approach, reference priority is given to reports considered to be of special importance for this more than two decades long process 'from bedside to bench to bedside'.